The Relationship Between Cognitive Ability in Mastery of Science Concepts and Innovative Ideas of Science Teaching for Prospective Elementary School Teachers - Andica Alvi Aulia Aulia (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2024)
Cognitive is a mental ability related to a person's knowledge, understanding, and intelligence. Broadly, cognitive includes the process of acquiring, structuring, and using knowledge. Cognitive can also be interpreted as the ability to learn, think, and solve simple problems, as well as the skill of understanding the surrounding environment. This study uses a descriptive qualitative approach with data collection techniques through interviews, to explore information from prospective PGMI teacher students at IAIN Sorong. The research can be concluded that a deep conceptual understanding of science provides benefits for prospective teachers and students. For aspiring teachers, a strong understanding of the basic concepts of science allows them to develop science learning that is more interesting, meaningful, and relevant for students. This includes the ability to explain material clearly, identify difficult concepts, make connections with real life, and design effective learning activities such as practicums, experiments, and science projects. For students, a good conceptual understanding can increase their enthusiasm, engagement, and understanding of science. In addition, a deep understanding also helps students develop critical and creative thinking skills. Thus, mastery of comprehensive basic science concepts plays an important role in improving the quality of science learning and developing students' potential